Better together: comprehensive social work education in England. (11th March 2022) - Hanley, Joe
Abstract : Prospective social workers in England are increasingly being segregated into different qualification routes. While the justification for this segregation relates to either academic achievement or the vocational nature of the course, students also end up segregated based on prior advantage, personal circumstances, context and experience. This article examines the three main routes into contemporary social work in England: fast-track training programmes, apprenticeships and mainstream programmes. It is shown that each of these approaches arguably have advantages and disadvantages, but that ultimately it is the segregation itself is doing the most damage to the profession. An alternative approach is suggested, based on comprehensive and social justice values, where the focus is on bringing students together, rather than splitting them apart.